Analysis of Illocutionary Acts in Classroom Interaction - Rahayu, Rahayu; Luthfiyati, Dian; Widyaiswara, Tiara; Shigemoto, Yuki (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
Interaction pattern is formed through speech acts uttered by lecturers and students as a means to achieve learning objectives. This study aims to identified the types of illocutionary acts expressed by the lecturer and students during class interaction in Class B of the English Education Department at Universitas Islam Lamongan. Using a qualitative descriptive method, data were obtained through non-participant observation and audio recordings. The recorded utterances were transcribed and examined based on speech act theory. A total of 384 utterances were documented, including 145 assertive, 187 directive, five commissive, and 47 expressive forms. The lecturer demonstrated four categories of illocutionary acts-assertive, directive, commissive, and expressive. While the students produced three: assertive, directive, and expressive. The results reveal the presence of various speech acts during classroom interaction. These findings can be used as a foundation for developing learning activities that foster student engagement and encourage the use of diverse speech acts.